Ad hoc networks connection availability modeling - Trajanov, Dimitar; Filiposka, Sonja; Marija Efnuseva; Grnarov, Aksenti (ACM, 2004)
One of the most important issues for mobile ad hoc networks is to know the availability of the system. In this paper we propose a generalized connection availability model based on real measurable parameters that concern the performances of mobile ad hoc networks. Detailed validation of the connection availability model is presented through simulations. The proposed model can be used for analysis or design of an ad hoc network that needs to satisfy a given connection availability level.
Keywords: Ad hoc Network, Connection Availability, Markov Chain.